HOMOGENEITY OF TITANIUM MANUFACTURED BY SOLID STATE CHIPS RECYCLING: Received: 01st May 2021; Revised: 18th September 2021, 12th November 2021; Accepted: 13th November 2021 - Topolski, Krzysztof (MATTER: International Journal of Science and Technology, 2021)
This work presents a promising method for recycling chips, carried out in the solid-state with the use of plastic working. High-purity (hp) titanium 99.99 chips after milling were subjected to a three-step procedure to transform these chips into a solid material. The objective of this work is to demonstrate the potential of this new processing method and to present the results of experiments conducted to determine the homogeneity of the final product. It was found that the processing method employed resulted in the formation of a solid and consolidated product in the form of a rod 8mm in diameter and 700mm long. The rod exhibited a grained microstructure typical of the Ti in the as-received state. Furthermore, the mechanical properties of the rod-product were also similar to those of titanium in the as-received state. For example, the hardness of the manufactured rod (average 97 HV10) was typical of the hardness of commercial Ti hp (94 HV10). In addition, the product obtained was characterized by adequate homogeneity in terms of its microstructure and mechanical properties. It was also found that the recycled material is as homogeneous as the commercial, reference Ti in the as-received state.